DESAIN DAN UJI COBA E-LKPD BERBASIS INTRODUCTION CONNECT APPLY REFLECT EXTEND (ICARE) PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Tika Arwina; Heppy Okmarisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research was instigated by the lack of available teaching material that was appropriate with student need—a teaching material connected the concept implementation to daily life. This research aimed at designing valid ICARE based electronic student workbook on Electrolyte and non-Electrolyte Solution lesson based on the validation by media and material experts, the teacher and student practicality tests. It was Research and Development (R&D) with Borg and Gall development design, and the steps were (1) researching and collecting information, (2) planning, (3) developing the initial form of the product, and 4) preliminary field testing, and (5) revising the product. Preliminary field testing was conducted to the eleventh-grade students of MIPA at State Senior High School located in Kampar district. The validation result by media and material experts showed that the score was 94.13% with very valid criterion. Teacher practicality test showed that the result was 93.63% with very practical category, and student practicality test showed that the result was 84.54% with very practical category.